2007
DOI: 10.1021/nl070728e
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Phosphide Nanowires as a Substrate for Cultured Neurons

Abstract: Dissociated sensory neurons were cultured on epitaxial gallium phosphide (GaP) nanowires grown vertically from a gallium phosphide surface. Substrates covered by 2.5 microm long, 50 nm wide nanowires supported cell adhesion and axonal outgrowth. Cell survival was better on nanowire substrates than on planar control substrates. The cells interacted closely with the nanostructures, and cells penetrated by hundreds of wires were observed as well as wire bending due to forces exerted by the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
185
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(193 citation statements)
references
References 27 publications
8
185
0
Order By: Relevance
“…Building on the previous observation that vertically grown NWs can support cell culture (15)(16)(17)(18)(19), we show that vertical NW substrates can serve as a universal, scalable, and highly efficient modality for introducing DNAs, RNAs, peptides, proteins, and small molecules into both immortalized and primary cell types, without chemical modification or viral packaging. This simplicity and generality, which stem from the direct physical access to the cell's interior afforded by NW penetration (15)(16)(17)(18)(19), make NW-based delivery distinct from chemical and viral methods that are widely employed (1)(2)(3)(4)(5)(6). Furthermore, this NW-based system is fully compatible with standard microarray printing techniques, allowing large collections of biomolecules to be delivered, or even codelivered, into live cells in a parallel and miniaturized fashion.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Building on the previous observation that vertically grown NWs can support cell culture (15)(16)(17)(18)(19), we show that vertical NW substrates can serve as a universal, scalable, and highly efficient modality for introducing DNAs, RNAs, peptides, proteins, and small molecules into both immortalized and primary cell types, without chemical modification or viral packaging. This simplicity and generality, which stem from the direct physical access to the cell's interior afforded by NW penetration (15)(16)(17)(18)(19), make NW-based delivery distinct from chemical and viral methods that are widely employed (1)(2)(3)(4)(5)(6). Furthermore, this NW-based system is fully compatible with standard microarray printing techniques, allowing large collections of biomolecules to be delivered, or even codelivered, into live cells in a parallel and miniaturized fashion.…”
mentioning
confidence: 52%
“…Previous studies have shown that vertical NWs spontaneously penetrate cells' membranes when cells are placed on top of the NWs (15)(16)(17)(18)(19). To visualize this penetration process, DiDmembrane-labeled HeLa cells (Magenta) were seeded on a bed of Si NWs whose gold tips had been prelabeled with This article contains supporting information online at www.pnas.org/cgi/content/full/ 0909350107/DCSupplemental.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Shalek et al reported the use of vertical silicon nanowires to deliver biomolecules such as proteins and DNA plasmids into living cells that grew attached to the nanowires (9). Together with other works that show vertical nanowires can support cell culture (10)(11)(12)(13)(14), these observations suggest a new and exciting possibility of using vertical nanowires as a universal platform to probe intracellular molecular events.…”
mentioning
confidence: 86%
“…26,[31][32][33][34][35] Second, cell proliferation/adhesion are not seriously affected by surficial compositions, other than surficial topographies. [67][68][69] In addition, histological inflammation and infection do not easily occur with sterilized extraneous objects without the involvement of germs, viruses, or macroscopic stabs.…”
Section: Apl Mater 5 074102 (2017)mentioning
confidence: 99%